An approach to develop a digital twin for industry 4.0 systems: manufacturing automation case studies. Issue 9 (2nd September 2021) - Guerra-Zubiaga, David; Kuts, Vladimir; Mahmood, Kashif; Bondar, Alex; Nasajpour-Esfahani, Navid; Otto, Tauno
ABSTRACT: The new paradigm of digital manufacturing and the concept of Industry 4.0 has led to the integration of recent manufacturing advances with modern information and communication technologies. Therefore, digital simulation tools fused into production systems can improve time and cost-effectiveness and enable faster, more flexible, and more efficient processes to produce higher-quality goods. The advancement of digital simulation with sensory data may support the credibility of production systems and improve the efficiency of production planning and execution processes. In this paper, an approach is proposed to develop a Digital Twin of production systems in order to optimize the planning and commissioning process. The proposed virtual cell interacts with the physical system with the help of different Digital Manufacturing Tools (DMT), which allows for the testing of various programs in a different scenario to check for any shortcomings before it is implemented on the physical system. Case studies from the different production systems are demonstrated to realize the feasibility of the proposed approach.